EMPOWERMENT STRATEGY OF VILLAGE COMMUNITY BASED ON FRESHWATER AQUACULTURE - Dewi Ayu Hidayati; Tina Kartika; Mohammad Muhassin (Universitas Padjadjaran, 2021)
Community empowerment is how to make people have the ability and independence in utilizing the existing potentials. In Banding Agung Village, Pesawaran Lampung, the abundant water resources available can be used for freshwater aquaculture activity as a strategy for empowering the community. The study aims to explore the strategies of community empowerment based on freshwater aquaculture activity, and to find out the factors inhibiting the community empowerment. This is a kind of descriptive qualitative research using case study framework. The data were collected through in-depth interviews, observation, and documentation and analyzed qualitatively employing data reduction, data display, and data verification. The findings indicated that some strategies have been implemented in empowering the community based on the freshwater aquaculture activity, consisting of building the community awareness on the importance of fish farming group (pokdakan), building institutional capacity through education, training and workshop of fish farming management, and putting group members’ knowledge and skill into practice. In the implementation of the strategies, some obstacles were found as the factors inhibiting the community empowerment, namely lack of community participation, lack of knowledge and capital, minimum assistance and counseling, and less involvement of the village government. The study recommends several alternative actions for a better implementation of the community empowerment.